Combining active and passive wind tunnel tests to determine the aerodynamic admittances of a bridge girder. Issue 231 (December 2022) - Wu, Bo; Zhou, Jianting; Li, Shaopeng; Xin, Jingzhou; Zhang, Hong; Yang, Xianyi
Abstract: In conventional buffeting analyses for long-span bridges, the aerodynamic admittance functions (AAF) with respect to the longitudinal (u-) and vertical (w-) turbulence components are usually assumed to be equivalent. This assumption could cause unpredictable errors due to complicated turbulence-structure interactions. This study proposes an experimental method to determine the u- and w- AAFs in the framework of three-dimensional buffeting theory. First, passive wind tunnel test is conducted to measure necessary aerodynamic parameters. Next, the turbulence characterized only by u-velocity fluctuations is generated in a multi-fan active-controlled wind tunnel to reproduce the u-velocity component in the passive wind tunnel test. The aim is to identify the u-AAF separately. Finally, the w-AAF is evaluated by combining the parameters measured in the active and passive wind tunnel tests. For a streamlined bridge girder, results show significant discrepancies between the u-AAF and w-AAF. The derivation degrees depend on the frequency and the angle of attack (AoA). This indicates the inaccuracy of the conventionally invoked assumption. In detail, the w-AAF is higher than the u-AAF at low frequencies, whereas the relationship reverses at higher frequencies. The proposed method is also applicable for other bluff-body structures, it is useful for improving the accuracy of buffeting analyses. Graphical abstract: Image 1 Highlights: A theoretical framework is derived to determine the AAFs with respect to u- and w-turbulence components. The three-dimensional effects of turbulence are considered in the theoretical framework. The theoretical framework is realized by combining active- and passive-wind tunnel tests. The u-component in the active-wind tunnel test is adjusted to reproduce that in the passive wind tunnel test. Comparisons between the u- and w-AAFs of a bridge deck directly indicate the inaccuracy of the equivalent-AAF assumption.